2007
DOI: 10.1016/j.jacc.2007.04.090
|View full text |Cite
|
Sign up to set email alerts
|

ST-Segment Deviation Analysis of the Admission 12-Lead Electrocardiogram as an Aid to Early Diagnosis of Acute Myocardial Infarction With a Cardiac Magnetic Resonance Imaging Gold Standard

Abstract: In patients admitted to hospital with possible AMI, the consideration of both ST-segment elevation and depression in the standard 12 lead-ECG recording significantly increases the sensitivity for the detection of AMI with only a slight decrease in the specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…As this and other studies show, a subgroup of NSTEMI patients have substantial infarction, 5,6 and there is a significant overlap in final infarct size between STEMI and NSTEMI patients. 6 Even patients with a normal ECG my develop large infarctions. 5 The latter corresponds to our findings, as only 7 of 13 patients (54%) with infarct size Ն12% had any evidence of ischemia in the ECG.…”
Section: Infarct Size In Nstemi Patientssupporting
confidence: 68%
See 1 more Smart Citation
“…As this and other studies show, a subgroup of NSTEMI patients have substantial infarction, 5,6 and there is a significant overlap in final infarct size between STEMI and NSTEMI patients. 6 Even patients with a normal ECG my develop large infarctions. 5 The latter corresponds to our findings, as only 7 of 13 patients (54%) with infarct size Ն12% had any evidence of ischemia in the ECG.…”
Section: Infarct Size In Nstemi Patientssupporting
confidence: 68%
“…ST-segment elevation in the ECG has high specificity but suboptimal sensitivity for detection of MI and acute coronary occlusion 3 and has demonstrated only modest correlation to infarct size. 4 A number of patients with non-ST-segment-elevation MI (NSTEMI) have substantial infarction, 5,6 but these patients rarely fulfill criteria for acute reperfusion therapy. In current clinical practice, no instant method for early assessment of final infarct size in patients with NSTEMI exists.…”
mentioning
confidence: 99%
“…According to this, it has been repeatedly shown that some NSTEMI patients may have a substantial infarction [2,6,7]. Also, some authors showed a significant overlap in the final infarct size between STEMI and NSTEMI patients [7] and others documented that even NSTEMI patients with a normal ECG at presentation may develop large infarctions [6]. On this basis, NSTEMI patients who have a substantial infarction should be promptly identified.…”
Section: Discussionmentioning
confidence: 91%
“…Both tracings depicted not only ST-segment elevation but also reciprocal ST-segment deviation, a finding reported to increase the sensitivity of MI detection on ECG. 1 The differential diagnosis for ST-segment elevation is broad, and includes pulmonary embolism, pericarditis, myocarditis, hyperkalemia, acute aortic dissection, pancreatitis, Brugada syndrome, gallbladder disease, antidepressant drug overdose, cardiac tumors, recent electrical cardioversion, or implantable cardioverter defibrillator shocks. 2 It is imperative to correlate the patient's clinical presentation with ECG findings when evaluating patients with chest pain or acute ST-segment abnormalities suggestive of acute ischemic ensure accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%